Blocking Oil Development in Yasuní National Park: Ecuador’s Unprecedented Strides Towards Environmental Justice - Prime, Lillian (Consilience, 2025)
This paper explores Ecuador’s proposal to protect Block 43 of the Yasuní National Park from oil drilling through the Yasuní-ITT Initiative proposed in 2007. The paper will examine why the initiative failed and how community activists responded. Ultimately, it will argue that the Yasuní-ITT Initiative upheld environmental justice through its assertion of a moral economy and its potential to help Ecuador step away from oil dependency and protect the rights of Indigenous communities, particularly the two tribes living in voluntary isolation in the Yasuní region. When the initiative was terminated and Indigenous communities were not consulted in the decision to begin drilling for heavy crude oil, citizen activism and mobilization of democracy through a referendum reasserted environmental justice and Indigenous rights.